Genetic and antigenic analyses of H5N8 and H5N1 subtypes high pathogenicity avian influenza viruses isolated from wild birds and poultry farms in Japan in the winter of 2021–2022 - SODA, Kosuke; MEKATA, Hirohisa; USUI, Tatsufumi; ITO, Hiroshi; MATSUI, Yuto; YAMADA, Kentaro; YAMAGUCHI, Tsuyoshi; ITO, Toshihiro (Journal of Veterinary Medical Science, 2023)
In the winter of 2021–2022, multiple subtypes (H5N8 and H5N1) of high pathogenicity avian influenza viruses (HPAIVs) were confirmed to be circulating simultaneously in Japan. Here, we phylogenetically and antigenically analyzed HPAIVs that were isolated from infected wild birds, an epidemiological investigation of affected poultry farms, and our own active surveillance study. H5 subtype hemagglutinin (HA) genes of 32 representative HPAIV isolates were classified into clade 2.3.4.4b lineage and subsequently divided into three groups (G2a, G2b, and G2d). All H5N8 HPAIVs were isolated in early winter and had HA genes belonging to the G2a group. H5N1 HPAIVs belong to the G2b and G2d groups. Although G2b viruses were widespread throughout the season, G2d viruses endemically circulated in Northeast Japan after January 2022. Deep sequence analysis showed that the four HPAIVs isolated at the beginning of winter had both N8 and N1 subtypes of neuraminidase genes. Environmental water-derived G2a HPAIV, A/water/Tottori/NK1201-2/2021 (H5N8), has unique polymerase basic protein 1 and nucleoprotein genes, similar to those of low pathogenicity avian influenza viruses (LPAIVs). These results indicate that multiple H5 HPAIVs and LPAIVs disseminated to Japan via transboundary winter migration of wild birds, and HPAIVs with novel gene constellations could emerge in these populations. Cross-neutralization test revealed that G2a H5N8 HPAIVs were antigenically distinct from a G2b H5N1 HPAIV, suggesting that antibody pressure in wild birds was involved in the transition of the HPAIV groups during the season.